2006
DOI: 10.1016/j.febslet.2005.12.072
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2D maps and coupling numbers for protein sequences. The first QSAR study of polygalacturonases; isolation and prediction of a novel sequence from Psidium guajava L.

Abstract: The development of 2D graph-theoretic representations for DNA sequences was very important for qualitative and quantitative comparison of sequences. Calculation of numeric features for these representations is useful for DNA-QSAR studies. Most of all graph-theoretic representations identify each one of the four bases with a unitary walk in one axe direction in the 2D space. In the case of proteins, twenty amino acids instead of four bases have to be considered. This fact has limited the introduction of useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 57 publications
2
120
0
1
Order By: Relevance
“…Indicative examples are presented in a number of research papers (see [1, 43, 53, 55-59, 60-62, 65-66, 69-103]). Several excellent reviews of these results can also be found in [104][105].…”
Section: Polynucleotidesmentioning
confidence: 99%
“…Indicative examples are presented in a number of research papers (see [1, 43, 53, 55-59, 60-62, 65-66, 69-103]). Several excellent reviews of these results can also be found in [104][105].…”
Section: Polynucleotidesmentioning
confidence: 99%
“…We have been following a recently introduced methodology, analogous to the DNA representations of Nandy, but adapted to the protein study (Aguero-Chapin et al, 2006). Depending on the characteristics of the amino acids, the method groups the 20 types of amino acids in four groups: polar, non-polar, acid or basic amino acids.…”
Section: Hp Lattice Network Representationmentioning
confidence: 99%
“…Thus, the information contained in biopolymeric long strings is simplified in a graph considering some of its relevant features as the topology and properties of the monomers. These factors determine either the approximated secondary structure [21] or the artificial, but informative, folding of linear sequences [22]. TI2BioP allows the calculation of the spectral moments derived from such inferred and artificial 2D structures of DNA, RNA and proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The calculation of the spectral moments as TIs is performed according the TOPS-MODE approach [13] and the pseudo-secondary structures for the protein sequences were taken from the experiences achieved by using the MARCH-INSIDE methodology [22; 24]. We used the 2D lattice of Hydrophobicity (H) and Polarity (P) introduced 6 by our group to encode information about polygalacturonases enzymes [22] to obtain the protein pseudosecondary structures.…”
Section: Methodsmentioning
confidence: 99%